Evaluation of the quality of cow milk consumed by children in and around Bahir Dar - Shiferaw, Fanaye; Mengistu, Ashenafi; Terefe, Getachew; Mazengia, Hailu (Ethiopian Journal of Science and Technology, 2025)
The safety of dairy products with respect to food-borne diseases is a great public health concern around the world. The microbial load of milk is a major factor in determining its quality. Hence, this study was aimed to evaluate of the quality and hygienic practices of cow milk consumed by children in and around Bahir Dar. A total of 79 milk samples were collected and analyzed using standard bacteriological examination. The study revealed that the proportions of respondents who practice udder washing prior to milking were 56%, 22% and 2% in urban, periurban and rural areas, respectively. Moreover, 88.7%, 67.3% and 45.2% of respondents has a practice of milk boiling before feeding the milk to their children in the urban, peri-urban and rural areas of the study, respectively. The majority of respondents in the urban (88%) and peri-urban (50%) areas wash milking, milk feeding and storing containers with detergents and boiled water. Higher (SPC/ml) was found in the rural 5x105 areas of the study compared to the urban and peri-urban sites. Likewise, of SPC, higher CC (2.2x105) was obtained in the rural area of the study without significant (p > 0.05) difference in mean SPC across location. Therefore, milk collected from all study sites does not meet the minimum quality standard as the coliform population was much higher than the value indicated. Therefore, further research works to address constraints and to improve child milk consumption are imperative.